Compressible large eddy simulation of the unsteady evolution process in a LPT Cascade with incoming wakes. (August 2021) - Wang, Yunfei; Chen, Huanlong; Liu, Huaping; Song, Yanping; Chen, Fu
An in-house large eddy simulation (LES) code based on three-dimensional compressible N-S equations is used to research the impact of incoming wakes on unsteady evolution characteristic in a low-pressure turbine (LPT) cascade. The Mach number is 0.4 and Reynolds number is 0.6 × 10 5 (based on the axial chord and outlet velocity). The reduced frequency of incoming wakes is Fred  = 0 (without wakes), 0.37 and 0.74. A detailed analysis of Reynolds stresses and turbulent kinetic energy inside the boundary layer has been carried out. Particular consideration is devoted to the transport process of incoming wakes and the intermittent property of the unsteady boundary layer. With the increase of reduced frequency, the inhibiting effect of wakes on boundary layer separation gradually enhances. The separation at the rear part of the suction side is weakened and the separation point moves downstream. However, incoming wakes lead to an increase in dissipation and aerodynamic losses in the main flow area. Excessive reduced frequency ( Fred  = 0.74) causes the main flow area to become one of the main source areas of loss. An optimal reduced frequency exists to minimize the aerodynamic loss of the linear cascade.